Control Flow Protection Against Return Oriented Attacks - Rincón, Álvaro; Boccardo, Davidson; Pirmez, Luci; Rust, Luiz Fernando (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2015)
Recent ROP (Return Oriented Programming) attacks are characterized by evading traditional protection methods, encouraging the scientific community to seek for a reliable and practical security solution. This work presents a novel technique based on control flow protection, and with a low overhead, making it suitable for constrained architectures in terms of processing, storage and energy. A prototype of the protection technique was developed and tested for ARM-Linux environment. The results show that our solution is effective and capable of preventing such ROP attacks with negligible overhead.